The “wall of text” visual structure of academic conference posters - Faulkes, Zen (Frontiers in Communication, 2023)
Posters created for conferences are a type of visual communication that are used frequently by academics. There are rarely any formatting requirements beyond fitting on their provided boards. Because posters are usually created by researchers rather than experienced graphic designers, the visual structure of conference posters may be influenced by the common format for journal articles, where text is given primacy over graphics and structured as “introduction, methods, results, discussion.” To test this, I examined award-winning posters from a large scientific society over 5 years of meetings. About three-quarters use the “Introduction, methods, results, discussion” format common to journal articles; about two-thirds use a columnar layout; most show multiple graphs and cite multiple references. Relatively few posters follow best graphic design practices, resulting in a “wall of text” on many posters.